Hindfoot endoscopic release of the posterior ankle capsuloligamentous structures improves ankle dorsiflexion range, function and pain in patients with painful limitation of ankle dorsiflexion. Issue 1 (22nd January 2020) - Hickey, Benjamin; Dalmau-Pastor, Miquel; Karlsson, Jón; Calder, James
Abstract : Objective: To evaluate the effect of arthroscopic release of the posterior capsuloligamentous structures on ankle dorsiflexion and function in patients with painful limitation of ankle dorsiflexion. Methods: A prospective consecutive case series of 13 adult patients with painful limitation of ankle dorsiflexion were included. None had clinically relevant gastrocnemius, soleus or Achilles contracture. Patients with anterior bony impingement or ankle degeneration on CT scan were excluded. All patients underwent combined anterior and posterior ankle arthroscopies with resection of posterior capsuloligamentous structures and the posterior fibulotalocalcaneal ligament. Ankle range of motion was assessed 2 years postoperatively. Foot and Ankle Outcome Scores (FAOS) were used to assess functional outcome. Results: The median patient age at surgery was 26 years (range 19–44). At 2 years postsurgery, the ankle dorsiflexion range had increased by 15 degrees (range 0–25, p<0.0001). FAOSs completed at a median of 44 months postsurgery (range 26–72) significantly improved. Median improvements were 19 points for pain (range 6–67, p=0.0004), 14 points for symptoms (range 0–36, p=0.0005), 15 points for activities of daily living (range 6–35, p<0.0001), 45 points for sport (range 20–55, p<0.0001) and 50 points for quality of life (range 13–62, p<0.0001). Conclusions: Hindfoot endoscopic release of the posterior ankle structures, including the posterior fibulotalocalcaneal ligament, is an effective technique for improving ankle dorsiflexion range in patients with painful limitation of ankle dorsiflexion. Level of evidence: IV.